Politik Hukum Pembaruan Undang-Undang Nomor 9 Tahun 1961 Tentang Pengumpulan Uang Atau Barang Dalam Kegiatan Filantropi Di Indonesia - Rr. Dyah Citra Harina (Lex Renaissance, 2019)
Philanthropy based on Law No. 9 of 1961 on Collection of Money or Goods. But as the times evolve, Law No. 9 of 1961 is considered as a weak legal basis for the implementation of philanthropy in Indonesia. Whilst on the other hand, the funds collected through philanthropic activities have the potentials to support the achievement of Sustainable Development Goals. Therefore, the focus of this study discusses: 1) How the legal policy of reforming Law No. 9 of 1961 on Collection of Money or Goods in philanthropic activities in Indonesia; 2) How is the renewal of Law No. 9 of 1961 in philanthropic activities in Indonesia to support the achievement of SDGs 2030. This is a normative study and analyzed using descriptive analysis. This research concludes that the reform of Law No. 9 of 1961 can not be separated from other elements outside the law that have a role in the occurrence of changes in society. Legal certainty is emphasized in order to achieve justice. In addition, the responsiveness of the lawmakers is also needed in order to update Law No. 9 of 1961 can support the achievement of TPB nationally.